Early surgical outcomes after total hip replacement in systemic lupus erythematosus patients - V. V. Mukhanov; S. A. Makarov; M. A. Makarov; T. V. Popkova (Научно-практическая ревматология, 2020)
Objective. To analyze early surgical outcomes after total hip replacement in systemic lupus erythematosus (SLE) patients.Subjects and Methods. The study included 42 SLE patients with femoral head osteonecrosis (ON) undergoing 59 total hip replacement (THR) surgeries at the traumatology and orthopedics department of VA Nasonova Research Institute of Rheumatology during 1998-2013 yy. All patients were thoroughly evaluated at baseline and one year after surgery using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K), damage index (DI) of the Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) to assess the degree of irreversible organ damage, Harris hip function scale, and VAS for pain intensity to assess early results of THR procedure.Results. Significant improvement of pain intensity was documented based on VAS assessments, as well as hip function improvement from 40,0±14,9 (13,8 – 82,7) to 80,8±12 (46,7-96,0) scores based on Harris scale, improvement of SLE activity based on SLEDAI-2K assessment: from 0 -20 scores (median 4[4;8]) at baseline to 0 – 43 scores (median 0[0;4]) at one year, and DI – from 0-12 (median 3[2;5]) to 0 -15 scores one year after THR procedure. Complications including dislocation of femoral component, peroneal nerve paralysis, periprosthetic fracture, venous thrombosis, and delayed wound healing were documented totally in 10,2% of patients. No post-surgery deaths occurred.Conclusion. The results obtained are indicative of better pain control and improved hip function following THR in SLE patients.